Comparing the interactions of DNA, polyamide (PNA) and polycarbamate nucleic acid (PCNA) oligomers with graphene oxide (GO) - Kotikam, Venubabu; Fernandes, Moneesha; Kumar, Vaijayanti Anil (Physical Chemistry Chemical Physics, 2012)
The fluorescently labelled short octameric oligothymine sequences of DNA, PNA and PCNA were used in fluorescence quenching studies in conjunction with dispersed graphene oxide. The measurable restoration of their fluorescence by complementary oligodeoxyadenylate was compared. This is the first study aimed at replacing the natural DNA probes with synthetic DNA mimics that show excellent properties in terms of formation of very strong duplexes with cDNA in addition to their stability towards proteases and nucleases.